Surgery of a Posterior Communicating Artery Aneurysm with Fetal-Type Circulation - González, Nicolás; Morales, Manuel; Ravera, Franco; Ruiz-aburto, Arturo; Vásquez, Juan; Muller, José; Mosquera, Jhon; Zapata, Rodrigo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Inadvertent occlusion of a fetal-type posterior communicating artery in aneurysm surgery could result in posterior circulation infarction and neurological morbidity. The case of a patient with an unruptured posterior communicating artery aneurysm with lateral projection and a fetal-type posterior communicating artery is presented. The utility of the carotid-oculomotor window as a surgical corridor to safely find the fetal-type posterior communicating artery is discussed.
Keywords: aneurysm; posterior communicating artery; circle of Willis; microsurgery